Pola Asuh Orang Tua dalam Ibadah Sholat Lima Waktu Anak Usia 7-10 Tahun - Tanti Sulastri; Sobar Al Ghazal; Ikin Asikin (UNISBA Press, 2022)
Abstract. A distinct Islamic Educationcan make someone's character to be a better one , thus will influence them to have a clear doctrine/lesson that can be implemented in their daily lives. As parents , it is a must to provide the best guidance in everything connected to religion. As parents should provide the best guidance or nurture in religious. In daily, many parents did not know how their children are doing worship, they ignore how important it is. Based on the case, the researcher interests to research about